2014
DOI: 10.1038/nature13229
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic targeting of BET bromodomain proteins in castration-resistant prostate cancer

Abstract: Men who develop metastatic castration-resistant prostate cancer (CRPC) invariably succumb to the disease. The development and progression to CRPC following androgen ablation therapy is predominantly driven by unregulated androgen receptor (AR) signaling1-3. Despite the success of recently approved therapies targeting AR signaling such as abiraterone4-6 and second generation anti-androgens MDV3100 (enzalutamide)7,8, durable responses are limited, presumably due to acquired resistance. Recently JQ1 and I-BET, tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

60
913
4
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 840 publications
(997 citation statements)
references
References 41 publications
60
913
4
2
Order By: Relevance
“…8 Furthermore, inhibition of BET bromodomain by small-molecule compounds with high potency against BET proteins, such as JQ1, results in significant downregulation of c-Myc as well as other transcription factors, and display antitumor activity in a variety of preclinical animal models of human cancers. [9][10][11][12] Importantly, these studies have established the feasibility of BET inhibition within an acceptable therapeutic window of tolerability. As a result, similar small molecules are currently in Phase I clinical trial for haematopoietic malignancies and advanced solid tumors (ClinicalTrials.…”
Section: Introductionmentioning
confidence: 99%
“…8 Furthermore, inhibition of BET bromodomain by small-molecule compounds with high potency against BET proteins, such as JQ1, results in significant downregulation of c-Myc as well as other transcription factors, and display antitumor activity in a variety of preclinical animal models of human cancers. [9][10][11][12] Importantly, these studies have established the feasibility of BET inhibition within an acceptable therapeutic window of tolerability. As a result, similar small molecules are currently in Phase I clinical trial for haematopoietic malignancies and advanced solid tumors (ClinicalTrials.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of BET inhibitors in tamoxifen-resistant breast cancer parallels our recent report of their effectiveness in castration-resistant prostate cancer (CRPC) [6], which analogous to tamoxifen-resistant ER-positive breast cancer, continues to maintain steroid hormone dependence. We have shown that the N-terminal region of BRD2/3/4 containing the BD1-BD2 domains physically interacts with the N-terminus of the Androgen Receptor (AR) and that this interaction is disrupted by JQ1.…”
mentioning
confidence: 51%
“…Examples of these include BET inhibitors, recently demonstrated to be effective in pre-clinical models of CRPC and antisense oligonucleotides, capable of inhibiting AR-mediated DNA transcription, currently in early phase clinical trials (NCT02122051). 22,23 Increased understanding of the interaction between AR and other oncological pathways, such as the PI3K-PTEN-AKT pathway, provides another rationale for alterative therapeutic approaches. PTEN loss is seen in around 40% of CRPC patients and is associated with shorter overall survival and earlier treatment failure with abiraterone.…”
Section: Mechanisms Of Resistancementioning
confidence: 99%